Fruit processing in Haiti - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Fresh fruit is difficult to transport successfully from the rural areas where it is produced to the urban centres where demand is greatest, but it can be processed into many products which store well. However, there are a number of technical and...